Health systems strengthening efforts help to improve the delivery of maternal nutrition interventions in antenatal care in Uttar Pradesh (UP), India but gaps remain - Kachwaha, Shivani; Nguyen, Phuong Hong; Tran, Lan Mai; Avula, Rasmi; Young, Melissa F.; Menon, Purnima (American Society for Nutrition, 2020)
Frontline workers (FLWs) deliver essential nutrition services to reduce maternal undernutrition in India, but coverage and quality remain sub-optimal. Alive & Thrive aimed to strengthen delivery of interpersonal counselling, community mobilization and micronutrient supplements through the government antenatal care (ANC) platform in UP. We studied pathways through which the nutrition-intensified ANC (I-ANC) was intended to impact FLWs capacity, knowledge, and service delivery, compared to standard ANC (S-ANC).